2018
DOI: 10.1177/0013161x18809343
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Open Enrollment and School Bond Voting

Abstract: Purpose: The purpose of this study was to identify an association between student mobility through open enrollment and voter support for school bond proposals. Specifically, we hypothesized that higher percentages of nonresident enrollment in a school district and resident exit from a district would be associated with lower levels of voter support for bond proposals. Data Collection and Analysis: We utilized publicly available data on bond proposals placed on ballots between 2009 and 2015, publicly available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…2. Pogodzinski et al (2019) also found that non-resident enrollment in metro Detroit may not be associated with resident voters' support for school bond proposals. 3.…”
Section: Notesmentioning
confidence: 93%
“…2. Pogodzinski et al (2019) also found that non-resident enrollment in metro Detroit may not be associated with resident voters' support for school bond proposals. 3.…”
Section: Notesmentioning
confidence: 93%